A study of the nature and origin of the minialbumins to be found in cadmium-poisoned animals - Sutherland, Elizabeth Mary (Adolescent Health Research Institute, 2020)
Cadmium, one of the trace metals, has, in the last two to three decades, become increasingly important in both industrial and biological fields. The recognition of cadmium as a serious health hazard has led to a closer examination of its properties and biochemical effects. Cadmium, an element of ata:nic number 48, atomic weight 112.41 and valency 2, is a soft 'White lustrous metal belonging to the second sub-group of the Periodic Table. It has a boiling point of 768°c, melting point of 321°0, is remarkably volatile for a heavy metal, and exists naturaly as a mixture of eight isotopes, constituting 2 x 10-5% of the earth's crust. Extraction of cadmium is by distillation from zinc ores. The electron configuration of cadmium is 4d105s2, and it forms simple bipositive cations only. There are no ligand field stabilization effects in cadmium ions, and the stereochemistry is, therefore, determined solely by size and electrostatic and covalent bonding forces.s Cadmium chloride shows octahedral co-ordination.